Thirty Years of Aquatic Mammal Research in Central America - May-Collado, Laura J.; Quintana-Rizzo, Ester (Revista de Biología Tropical, 2023)
The editors of the Special Issue began their careers as aquatic mammal biologists in the early 90s. At that time, aquatic mammals were not considered essential to Central America’s marine or mammalian community (including Panama). Aquatic mammals are charismatic megafauna that can become symbols of conservation, though the significance of their contribution to a particular habitat is often misrepresented. Over the past decade, their importance in this region has become evident as Central America’s Pacific and Caribbean waters are home to about 30% of the world’s cetacean diversity (May-Collado, 2009; May-Collado et al., 2018). This knowledge results from a growing community of national and international scientists that, together, reveal aquatic mammals’ extraordinary ecology and contribution to the region’s economy (i.e., Hoyd & Iñiguez, 2008; May-Collado et al., 2018).